Power and its Logic Politics and how to master it - Blum, Christian 1980-; Meier, Dominik 1969- (Edition Politik, 2019)
Power is the essence of politics. Whoever seeks to comprehend and master it, must understand its logic. Drawing on two decades of international experience in political consulting, Dominik Meier and Christian Blum give profound and honest insights into how power functions. Introducing their Power-Leadership Approach, the authors provide both a conceptual and a theoretical analysis of power and present the tools to successfully exercise power in the political domain. "The Logic of Power" is an enlightening guidebook for decision-makers in politics, business and civil society, for consultants and policy-advisers, students and scholars and for anyone looking to understand how power is constructed.